Ethiopia : A Woman Innovator Speaks - World Bank (World Bank, Washington, DC, 2012)
This note discusses about six farmer innovators from Ethiopia that took part in the recent international workshop on Promoting Local Innovation (PROLINNOVA), which was held in March 2004 at the Furra Institute of Development Studies in Yirgalem, Southern Ethiopia. Over 60 participants from Africa, Asia and Europe took part. They discussed experiences in building multi-stakeholder partnerships to promote participatory research and development that starts with recognizing the dynamics of indigenous knowledge. They visited farmer researchers and innovators in Southern Ethiopia and listened to the oral presentations of the farmers who came from more distant parts of the country.